A comprehensive concept of social innovation and its implications for the local context – on the growing importance of social innovation ecosystems and infrastructures. Issue 3 (3rd March 2020) - Domanski, Dmitri; Howaldt, Jürgen; Kaletka, Christoph
ABSTRACT: The significance of social innovations for successfully meeting social, economic, political and environmental challenges of the twenty-first century is recognized not only by stakeholders on the local, regional and even national level but also within the Europe 2020 strategy and on a global scale. However, despite this growing awareness, for a long time a sustained and systematic analysis of social innovation, its theories, characteristics and impacts was missing. In this setup, the paper seeks to contribute to a common theoretical ground in social innovation theory by elaborating on a comprehensive concept of social innovation grounded in social theory and discusses consequences for social innovations in the urban context. The paper starts with an outline of theoretical foundations of social innovation and investigates the relationship between social innovation and social change. It then discusses the consequences of a comprehensive concept of social innovation for the local level, highlighting its multi-sectoral perspective. Social innovation ecosystems are introduced as an emerging theoretical approach and heuristic model especially for urban social innovation. Here, results of a global mapping conducted by the international research project SI-DRIVE provide empirical insights into the diversity and current state of social innovation initiatives.